Allogeneic stem cell transplantation in multiple myeloma: immunotherapy and new drugs. (June 2015) - Festuccia, Moreno; Martino, Massimo; Ferrando, Federica; Messina, Giuseppe; Moscato, Tiziana; Fedele, Roberta; Boccadoro, Mario; Giaccone, Luisa; Bruno, Benedetto
<x xml:space="preserve">Abstract</x> Introduction: Autologous (auto) stem cell transplantation (SCT) and the development of new drugs have improved the survival of multiple myeloma (MM) patients. By contrast, though potentially curative, the use of allogeneic (allo)-SCT is controversial. Areas covered: A review has been conducted to examine the current evidence for the use of allo-SCT in MM. We have examined novel cell therapies that may be exploited to induce myeloma-specific immune responses including the new promising frontier of chimeric antigen receptor (CAR)-T and -natural killer (NK) cells. Expert opinion: One of the major controversies facing researchers in exploring the allo approach is the remarkable recent treatment improvement observed with second- and third-generation proteasome inhibitors and immunomodulatory drugs, monoclonal antibodies and deacetylase inhibitors. Despite these great advances, the disease remains to be incurable and allo-SCT may still play a role in the cure of MM. We think that allo-SCT conserves a role in MM and its curative potential in high-risk patients should be explored in the setting of control clinical trials. Novel cell therapies such as CAR technologies may open new avenues of research toward a potential cure. Data from currently ongoing prospective studies will be helpful to clarify pending clinical questions.